The Limiting Absorption Method for a Transmission Problem in Acoustic Scattering (Journal of Partial Differential Equations, 2020)
The limiting absorption principle is used to solve the scattering problem of time harmonic acoustic waves by penetrable objects in Sobolev spaces. The method is based on integral representation of the solution using the Green's kernel of the Helmholtz equation.
Keywords: Limiting absorption principle; Helmholtz equation; exterior domains; Sommerfeld radiation condition; Rellich lemma